Dynamic analysis of structures with Maxwell model. - Hatada, Tomohiko (Earthquake engineering & structural dynamics.)
A numerical method has been developed for the dynamic analysis of a tall building structure with viscous dampers. Viscous dampers are installed between the top of an inverted V-shaped brace and the upper beam on each storey to reduce vibrations during strong disturbances like earthquakes. Analytically, it is modelled as multi-degree of freedom (MDOF) system with the Maxwell models. First, the computational method is formulated in the time domain by introducing a finite element of the Maxwell model into the equation of motion in the discrete time system, which is based on the direct numerical integration. Next, analyses for numerical stability and accuracy of the proposed method are discussed. The results show its numerical stability. Finally, the proposed method is applied to the numerical analysis of a realistic building structure to demonstrate its practical validity.